Risk Factors for Dengue Fever in Sungai Pinang Subdistrict in Samarinda City - Apriyani Apriyani; Gilang Mahadani; Sulung Alfianto Akbar (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
Dengue hemorrhagic fever (DHF) is a disease spread by the Aedes aegypti mosquito, a species that reproduces very quickly and infects around 390 million people each year. The objective of this research is to identify risk factors associated with the occurrence of DHF in the village of Sungai Pinang, located in the city of Samarinda. This study employs a quantitative approach and uses an observational method with a case-control design, which allows for the analysis of the relationship between the disease or health condition and specific risk factors. The sample consisted of 74 participants, divided into 37 cases and 37 controls, selected through purposive sampling. Odds ratios were used for data analysis. The results indicated that the presence of a lid on the water container represented a risk factor (OR = 1.135; 95% CI: 0.424–3.039). Similarly, the habit of emptying water containers was shown to be a risk factor (OR = 1.556; 95% CI: 0.617–3.928), as was the type of container material (OR = 1.268; 95% CI: 0.487–3.301) for the incidence of dengue in the village of Sungai Pinang Dalam, Samarinda City. In conclusion, the water container cover, the practice of emptying it, and the container material were identified as factors that influence the occurrence of dengue cases in this area.